Long-term compositional and eruptive transitions in an early Miocene volcanic system, Central Chile (33°S) - Ítalo Payacán; Martín Meyer; Javier Reyes; Lorenzo Tavazzani; Rodrigo Quiroga; Javiera Muñoz; Francisco Gutiérrez; Sebastián Santibáñez (Journal of Volcanology and Geothermal Research, 2025)

Plant Trait Matching Occurs in Facilitative Interactions Across Global Drylands - Imke C. Smit; Peter C. le Roux; Santiago Soliveres; Nicolas Gross; Yoann Le Bagousse‐Pinguet; Hugo Saiz; Mehdi Abedi; Rodrigo Ahumada; Antonio I. Arroyo; Sergio Asensio; Richard Benoit; Niels Blaum; et al. (Global Ecology and Biogeography, 2025)
Aim Plant functional traits can influence interaction outcomes between nurse and target plants through a “functional trait match”, which occurs when the traits of nurse plants ameliorate their environment, and target plants possess traits that allow them to benefit from this ameliorated environment. We investigated how the traits of putative nurse species affect interaction outcomes across global drylands and determined the functional match that promotes facilitation. We also investigated how grazing pressure and global climatic and edaphic gradients affected this trait match. Location Global drylands. Time Period 2016–2019. Major Taxa Studied Vascular plants. Methods We used a collaborative survey conducted across 29 sites from five continents, where we gathered in situ co‐occurrences of dominant species (‘nurses’) and other vascular plant species, as well as their functional traits [plant height and leaf dry matter content (LDMC)]. Climate, edaphic variables and grazing pressure were measured in situ or extracted from databases. We used a model building approach to determine the effect of dominant plant traits on interaction outcomes, and how the functional trait match between nurse and target species is affected by environmental variables. Results Tall dominant plants with conservative leaves generally had a greater positive effect on species richness and cover beneath their canopies, but these effects were strongly modulated by grazing pressure and soil pH. Target plants that were significantly associated with dominant plants tended to be shorter, and have more acquisitive leaves than dominant plants, regardless of environmental conditions. However, the difference in height and LDMC between dominant plants and negatively associated target plants was strongly affected by environmental conditions. Main Conclusions Functional traits play a significant role in determining interaction outcomes between dryland plants. Facilitation in drylands is driven by a conservative‐acquisitive trait match, a pattern observed regardless of grazing pressure, climate and soil conditions.

Between oceans: stepping-stone dispersal and the Pacific-to-Atlantic expansion of Chinook salmon across Patagonia - Carla Riva-Rossi; Javier Ciancio; Daniel Gomez-Uchida; Miguel Pascual; Rodrigo Clarke; Pamela Quiroga; Cecilia Di Prinzio; Carolina Lázari; John Carlos Garza (Frontiers in Marine Science, 2025)
Introduction Biological invasions are major drivers of biodiversity loss worldwide, and salmonid introductions are among the most transformative events in the Southern Hemisphere. The rapid, large-scale expansion of Chinook salmon ( Oncorhynchus tshawytscha ) across South America, driven by high migratory capacity, straying rates, and genetic adaptability, constitutes an unprecedented salmonid invasion. In Patagonia, this spread is accelerating, yet the mechanisms enabling long-distance marine dispersal, successful freshwater colonization, and secondary expansion remain poorly understood. A recently established population in the De las Vueltas River (DLVR), an upper tributary of the Santa Cruz River in Argentine Patagonia, was examined as a key node in the invasion network connecting Pacific-origin populations with new Atlantic Ocean basins. Methods Two high-resolution SNP panels (96 and 172 loci) were used to investigate the genetic origins and colonization dynamics of the DLVR population. Tissue samples from 70 fish collected in 2014–2015 were genotyped and compared with North American source lineages to infer ancestral origins, and with Pacific and Atlantic naturalized populations to reconstruct recent invasion pathways. Discriminant analysis of principal components (DAPC), genetic mixture modeling, and Bayesian assignment implemented in the R package rubias were performed. Simulations were used to harmonize SNP data across panels and to improve assignment accuracy. Results The genetic roots of the DLVR population were traced to stocks from the Lower Columbia River fall and spring runs and the Willamette River spring run. Strong genetic affinities were detected with naturalized populations from Chile’s Aysén Region, particularly the Cobarde and Vargas Rivers, while smaller contributions from Santa Cruz River populations were inferred. These findings indicate colonization through long-distance oceanic or trans-Andean dispersal, followed by secondary expansion within the Santa Cruz basin. Discussion The role of ocean connectivity, stepping-stone habitats, and leading-edge dispersal in enabling the rapid eastward spread of Chinook salmon is highlighted by these results. The Santa Cruz River basin is identified as a critical invasion hub, concentrating propagules from multiple lineages and promoting multi-step dispersal into new Atlantic Ocean basins. These insights emphasize the need to incorporate riverine connectivity and invasion hubs into management strategies to mitigate the ecological and evolutionary impacts of Chinook salmon in South America.

How deformation shapes the Salar de Antofalla, southern Puna: Insights from a 4D kinematic-dynamic model - Laura Giambiagi; Julieta Suriano; Diego Jaldin; Lucas Lothari; Andrés Echaurren; Rodrigo Quiroga; Matías Barrionuevo; José Mescua; Macarena Bertoa del Llano; Ahmad Arnous (Tectonophysics, 2025)

Effects of the toxic dinoflagellate Protoceratium reticulatum and its yessotoxins on the survival and feed ingestion of Argopecten purpuratus veliger larvae - María Gabriela Nieves; Patricio A. Díaz; Michael Araya; Pablo Salgado; Rodrigo Rojas; Eduardo Quiroga; Gemita Pizarro; Gonzalo Álvarez (Marine Pollution Bulletin, 2024)

A novel missense mutation in the AIRE gene underlying autoimmune polyglandular syndrome type 1 - Susana Vitozzi; Silvia Graciela Correa; Alejandro Lozano; Eduardo Jorge Fernández; Rodrigo Quiroga (Immunogenetics, 2024)

Along strike variations on inverted Tarapacá Basin and its influence in buried western Andean mountain front building - Guillermo Fuentes; Sebastián Perroud; Walter Garrido; Rodrigo Quiroga; Fernando Martínez (Journal of South American Earth Sciences, 2023)

Richness, not evenness, varies across water availability gradients in grassy biomes on five continents - Melinda D. Smith; Sally E. Koerner; Meghan L. Avolio; Kimberly J. Komatsu; Stephanie Eby; Elisabeth J. Forrestel; Scott L. Collins; Kevin R. Wilcox; Rodrigo Ahumada; John W. Morgan; Gabriel Oliva; Gastón R. Oñatibia; et al. (Oecologia, 2022)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Synthesis of novel 7-aryl and 7-spiropyrazolo[4′,3′:5,6]pyrido[2,3-d]pyrimidine derivatives and their study as AChE inhibitors - Paola Acosta; Braulio Insuasty; Rodrigo Abonia; Margarita Gutierrez; Jairo Quiroga (Molecular Diversity, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Erratum to: Bayes optimal template matching for spike sorting – combining fisher discriminant analysis with optimal filtering - Felix Franke; Rodrigo Quian Quiroga; Andreas Hierlemann; Klaus Obermayer (Journal of Computational Neuroscience, 2015)

Bayes optimal template matching for spike sorting – combining fisher discriminant analysis with optimal filtering - Felix Franke; Rodrigo Quian Quiroga; Andreas Hierlemann; Klaus Obermayer (Journal of Computational Neuroscience, 2015)

Synthesis of 3-aryl-1,2,4-benzotriazines via intramolecular cyclization of solid-supported o-hydrazidoanilines - Edwar Cortés; Luciana Méndez; Ernesto G. Mata; Rodrigo Abonia; Jairo Quiroga; Braulio Insuasty (Molecular Diversity, 2012)

An efficient and reproducible protocol for production of AFLP markers in tree genomes using fluorescent capillary detection - Rodrigo Hasbún; Carolina Iturra; Priscila Moraga; Pamela Wachtendorff; Pamela Quiroga; Sofía Valenzuela (Tree Genetics & Genomes, 2012)

Molecular and genetic characterization of novel S-RNases from a natural population of Nicotiana alata - Juan A. Roldán; Rodrigo Quiroga; Ariel Goldraij (Plant Cell Reports, 2010)